Selat Melaka 1992 - 2006: Iktibar beberapa aspek permasalahan dalam mengurus kesejahteraan sumber sekitaran serantau - Amriah Buang, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2006)
The Malacca Strait is the main shipping channel between the Indian Ocean and the Pacific Ocean, linking major Asian economies such as India, China, Japan and South Korea as well as (Southeast Asian Association of Nations (ASEAN) countries, in particular, Malaysia, Indonesia and Singapore.In 2006, an estimated 15 million barrels per day (2,400,000 m3/d) of oil were transported through the strait in the midst of 34 ship wreck events. Piracy in the strait had been rising in the last decade - 25 attacks on vessels in 1994, 220 in 2000, and just over 150 in 2003 (one-third of the global total) - forcing the littoral states (Malaysia, Indonesia and Singapore) to resort to more advanced counter measures when attacks rose again in the first half of 2004 . Subsequently, attacks on ships in the Strait of Malacca dropped to 79 in 2005 and 50 in 2006 although the shipping industry was still harbouring fears of revival of attacks. Such was the ongoing challenge faced by the littoral states in managing the Malacca Strait as a regional environmental resource. This paper re-visits the situation in 1992 when the challenge was at one of its heaviest and recalls conclusively that the three factors of (1) cooperation among the littoral states inenhancing methods and techniques of managing the strait; (2) pro-active efforts on the part of the shipping companies to reduce vessel collisions by regular renewal and upgrading of gears and manpower; and (3) responsible involvement by international users of the strait in managing safety in the strait, are still pertinent in 2006 as they were in 1992